Taking Back Curriculum: Feminist Innovations towards Nonviolent Futures - Moorhouse, Emily (Atlantis)

(untitled) (Mount Saint Vincent University, 2024)
This paper maps key factors that activate adult stakeholders in Ontario to support curriculum pertaining to consent and non-violence in K-12 education. The paper draws from a study that used three qualitative approaches: (1) the design of an original media literacy curriculum module for Ontario youth ages 13-15; (2) curriculum assessment of the module by diverse stakeholders in Ontario K-12 education (n=20); and (3) analysis of archival documents pertaining to consent education and media literacy in Ontario, including official curriculum and media reports. Four key factors united stakeholders in supporting K-12 curriculum pertaining to consent and non-violence in Ontario. Firstly, stakeholders are intrigued by media-based pedagogies that can facilitate consent education that is “culturally relevant” (Ladson-Billings 1994; 1995) for diverse learners in Ontario. Stakeholders are also more likely to support consent and violence prevention initiatives if accompanied by professional development and teaching tools. Educator collectives and political organizing also allow for more feminist and social-justice pedagogies in the classroom, including consent education. Finally, parent councils and community groups are essential places for activism and knowledge sharing that can meet the needs of community members, while addressing stakeholders’ attitudes and behaviours that gatekeep violence prevention initiatives in education.